Science, Innovation, and Social Work: Clash or Convergence?. (March 2017) - Flynn, Marilyn L.
Social work as a human services profession has been distinctive for its inclusion of research as a required element of practice and instrument in instigating reform. At the present time, the relationship of social work to science and a redefinition of social work as a science have reentered our national dialogue with new force. This expansion of perspective has, however, failed to explicitly attend to a closely related intellectual and practical domain, the world of social innovation. Innovation as an end itself, a synonym for progress, has largely been owned by the professions of business, engineering, and the biosciences. This essay presents a discussion of how social work may engage with social innovation and the tensions inherent to such an engagement. A place for social innovation within the recognized domains of scientific investigation and social work is essential. Social work would make a unique contribution to the enhancement of this conception through the weight given to values, social purpose, and context that is endemic to the social work perspective. The result of combining science and social innovation perspectives in the same academic home might be a flowering of new social configurations, networks, organizations, and relationships disciplined by repeated appraisals through the scientific method.